2016
DOI: 10.1016/j.econmod.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Modelling events: The short-term economic impact of leaving the EU

Abstract: and Social Research is Britain's longest established independent research institute, founded in 1938. The vision of our founders was to carry out research to improve understanding of the economic and social forces that affect people's lives, and the ways in which policy can bring about change. Seventy-five years later, this remains central to NIESR's ethos. We continue to apply our expertise in both quantitative and qualitative methods and our understanding of economic and social issues to current debates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…In 2016, NIESR published some articles that explore the implications of leaving EU for UK economy. On short-term, Baker et al (2016b) have suggested that the level of GDP in 2017 would be 1% lower than the baseline forecast with UK in EU and by 2018 could get to 2.3%. On long-term, Ebell and Warren (2016) projected that by 2030, UK GDP would be 1.5% to 2.1% lower in a Norwegian scenario, 1.9% to 2.3% lower in a Swiss scenario, and 2.7% to 3.7% in the WTO scenario.…”
Section: Overall Economic Implications Of Brexit -The Impact On Gdpmentioning
confidence: 90%
See 1 more Smart Citation
“…In 2016, NIESR published some articles that explore the implications of leaving EU for UK economy. On short-term, Baker et al (2016b) have suggested that the level of GDP in 2017 would be 1% lower than the baseline forecast with UK in EU and by 2018 could get to 2.3%. On long-term, Ebell and Warren (2016) projected that by 2030, UK GDP would be 1.5% to 2.1% lower in a Norwegian scenario, 1.9% to 2.3% lower in a Swiss scenario, and 2.7% to 3.7% in the WTO scenario.…”
Section: Overall Economic Implications Of Brexit -The Impact On Gdpmentioning
confidence: 90%
“…For the pound sterling evolution, Baker et al (2016b) considered that the risk and uncertainty will cause a depreciation by around 20% immediately following the Referendum, determining inflationary pressure. Gerlach and Giamberardino (2016) estimated the potential size of the effect of UK's Referendum on pound sterling by looking at the relationship between daily changes in the pound exchange rate and bookmakers' odds of Brexit.…”
Section: Financial Issues and Brexitmentioning
confidence: 99%
“…2 Interest rate assumptions are based on information available for the period to 12 January 2017. 3 For discussions of the short and long-run economic implications of the UK leaving the EU see Baker et al (2016) and Ebell et al (2016) day. Projections from the EIA suggest around a 10 per cent, year-on-year increase in prices towards the end of 2018.…”
Section: Notesmentioning
confidence: 99%
“…For a discussion of fiscal multipliers and the impact of fiscal policy on the macroeconomy based on NiGEM simulations, see Barrell et al (2012). of the UK leaving the EU see Baker et al (2016) and Ebell et al (2016), respectively.…”
mentioning
confidence: 99%